Answer:
![5 * 10^{-8} m](https://tex.z-dn.net/?f=5%20%2A%2010%5E%7B-8%7D%20m)
Step-by-step explanation:
The speed of light is
and its frequency is
.
The speed of light is given as:
c = λ * f
where λ = wavelength of light
f = frequency of light
Therefore, the wavelength is given as:
λ = c / f
=> λ = ![\frac{3 * 10^8}{6 * 10^{15}}](https://tex.z-dn.net/?f=%5Cfrac%7B3%20%2A%2010%5E8%7D%7B6%20%2A%2010%5E%7B15%7D%7D)
=> λ = ![5 * 10^{-8} m](https://tex.z-dn.net/?f=5%20%2A%2010%5E%7B-8%7D%20m)
The wavelength of the light is ![5 * 10^{-8} m](https://tex.z-dn.net/?f=5%20%2A%2010%5E%7B-8%7D%20m)
Answer:
![y=\frac{-7t^2+22t-7}{7t-22}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-7t%5E2%2B22t-7%7D%7B7t-22%7D)
Step-by-step explanation:
We are given that
Initial value problem
, y(3)=4
Substitute the value ![z=t+y](https://tex.z-dn.net/?f=z%3Dt%2By)
When t=3 and y=4 then
z=3+4=7
![y'=z^2-1](https://tex.z-dn.net/?f=y%27%3Dz%5E2-1)
Differentiate z w.r.t t
Then, we get
![\frac{dz}{dt}=1+y'](https://tex.z-dn.net/?f=%5Cfrac%7Bdz%7D%7Bdt%7D%3D1%2By%27)
![z'=1+z^2-1=z^2](https://tex.z-dn.net/?f=z%27%3D1%2Bz%5E2-1%3Dz%5E2)
![z^{-2}dz=dt](https://tex.z-dn.net/?f=z%5E%7B-2%7Ddz%3Ddt)
Integrate on both sides
![-\frac{1}{z}dz=t+C](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7Bz%7Ddz%3Dt%2BC)
![z=-\frac{1}{t+C}](https://tex.z-dn.net/?f=z%3D-%5Cfrac%7B1%7D%7Bt%2BC%7D)
Substitute t=3 and z=7
Then, we get
![7=-\frac{1}{3+C}](https://tex.z-dn.net/?f=7%3D-%5Cfrac%7B1%7D%7B3%2BC%7D)
![21+7C=-1](https://tex.z-dn.net/?f=21%2B7C%3D-1)
![7C=-1-21=-22](https://tex.z-dn.net/?f=7C%3D-1-21%3D-22)
![C=-\frac{22}{7}](https://tex.z-dn.net/?f=C%3D-%5Cfrac%7B22%7D%7B7%7D)
Substitute the value of C then we get
![z=-\frac{1}{t-\frac{22}{7}}](https://tex.z-dn.net/?f=z%3D-%5Cfrac%7B1%7D%7Bt-%5Cfrac%7B22%7D%7B7%7D%7D)
![z=\frac{-7}{7t-22}](https://tex.z-dn.net/?f=z%3D%5Cfrac%7B-7%7D%7B7t-22%7D)
![y=z-t](https://tex.z-dn.net/?f=y%3Dz-t)
![y=\frac{-7}{7t-22}-t](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-7%7D%7B7t-22%7D-t)
![y=\frac{-7-7t^2+22t}{7t-22}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-7-7t%5E2%2B22t%7D%7B7t-22%7D)
![y=\frac{-7t^2+22t-7}{7t-22}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-7t%5E2%2B22t-7%7D%7B7t-22%7D)
Answer:
c = 17
Step-by-step explanation:
Use the Pythagorean Theorem to solve this problem.
The equation is a² + b² = c².
"a" and "b" are the length of the two shorter sides or values.
"c" is the length of the longest side or value, also the hypotenuse.
Since we know the two smaller values, we can <u>replace "a" and "b" with 8 and 15</u>. It does not matter which letter you decide to replace with which number.
Then<u> simplify and isolate "c" </u>to find the largest value.
a² + b² = c²
8² + 15² = c² Substitute "a" and "b". Square the numbers to simplify
64 + 225 = c² Add to simplify
289 = c²
√289 = √c² Square root both sides
√289 = c "c" will be isolated because √ and ² are reverse operations
c = √289 Put 'c' on the left side for standard formatting.
c = 17 Answer
Therefore the largest value, c, is 17 in the triple.
Answer:
3 h(x) = 4 sin(2x + π) + 3
Step-by-step explanation: